DISFEMISME WARGANET DALAM KOMENTAR DI INSTAGRAM PADA UNGGAHAN PILPRES 2019 - Fitriyana Fitriyana; Hasnah Faizah; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The results of this study are focused on the use of language in the form of rude expressions (dysphemism) with language that is not polite, not polite and in the form of curses delivered in the Instagram comments column about the 2019 presidential election. This research was included in a qualitative descriptive study. This research was obtained through observation of existing data. Based on the results of research and discussion of citizens' dysphemism in comments on Instagram in the 2019 presidential election uploads found 67 words in terms of word dysphemism, 23 terms in terms of phrase dysphemism, 10 in terms of idiomic dysphemisms in 10 data. The function of citizens' dysphemism in the comments on Instagram on the 2019 presidential election upload is divided into 7 functions namely, (1) protesters dislike or disagree with a person of 20 data, (2) an indicator of disrespect or denigrate another person by 26 data, ( 3) blasphemous or criticize as much as 8 data, (4) curse or curse as much as 16 data, (5) exaggerate something as much as 4 data, (6) comparison of humans with animals that are considered to have negative behavior as much as 6 data, (7) as the means to mock up as much as 20 data. Then the meaning of dysfemism in this study is divided into 5, namely, (1) insulting meanings of 22 data, (2) swearing meaning of 11 data, (3) the meaning of 13 speakers 'abusive statements, (4) the meaning of 26 speakers' annoyance statements , (5) the meaning of quiping as much as 28 data. Key Words: Form of Dysphemism, Dysphemism Function, Meaning Of Dysfemism